“Soft Power” of Academic Mobility as a Component of the Chinese Foresight Project of “The Great Unity” Society - Zakharov, Mikhail; Starovoytova, Irina; Shishkova, Anastasia (Տիգրան Մեծ)
The article considers the phenomenon of cross-border academic mobility in the context of Chinese predictive practice. By applying historical-philosophical, comparative and hermeneutic methods, the authors analyze three problem areas: the social ideal, forecasting the future, and national education in China – and make the following conclusions. The “prior knowledge” that came from the culture of Imperial China can be used as an element of modern prognostics, and the traditional project of the “Great Unity” society (the “Datong” society in the Confucian concept of the social ideal) is transformed into a national foresight project. At the same time, the idea of unified humankind is not exclusively Chinese but has deep historical roots and universal nature. Being cautious about the supranational extrapolation of this idea, modern China, nevertheless, is expanding international cooperation and strengthening international contacts, using cross-border academic mobility as one of the tools of “soft power”.
Keywords: Philosophy of economics